PROSPECTS FOR THE DEVELOPMENT OF DOMESTIC TECHNOLOGY TOURISM BUSINESS MODELS IN THE CONTEXT OF CHINA'S AGEING POPULATION - Difei He; Suraphong Wacharajit (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The tourist industry is one of the economy's fastest-growing sectors today, and its significance in fostering cross-cultural understanding is generally acknowledged. The tourist industry is a significant employer and major contributor to the world economy, accounting for around 10% of GDP. Recent years have seen a surge in China's technologically-driven, alternative tourism trend. As a result, new tourism-related industries have increased and become significant employer. However, the tourism industry is currently experiencing a time of uncertainty, waiting, and stagnation due to the ongoing COVID-19 Pandemic. In addition, the international tourism industry has had